Existence of Solutions for Optimal Control Problems on Time Scales whose States are Absolutely Continuous - Santos, I.l.d. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2016)
ABSTRACT This paper considers a class of optimal control problems on time scales described by dynamic equations on time scales. For this class, the states are absolutely continuous. We have established sufficient conditions for the existence of optimal controls.

RESUMO Este artigo considera uma classe de problemas de controle ótimo em escalas temporais descritos por equações dinâmicas em escalas temporais. Para essa classe, os estados são absolutamente contínuos. Nós estabelecemos condições suficientes para a existência de controles ótimos.
Keywords: Time scales; control systems; optimal control; escalas temporais; sistemas de controle; controle ótimo